Cardiac magnetic resonance as a risk re-stratification tool in apical hypertrophic cardiomyopathy - Larriva, Ana María (2023)
Apical hypertrophic cardiomyopathy (ApHCM) can result in the formation of a left ventricular apical aneurysm and progressive myocardial fibrosis, which is associated with a worse prognosis. We present the case of a 76-year-old man previously diagnosed with ApHCM seven years ago, who has been under clinical follow-up. Serial cardiac magnetic resonance (CMR) imaging was performed in 2013 and 2020 due to suspected apical aneurysm formation based on echocardiographic evaluation. The 2020 CMR imaging revealed an increase in myocardial fibrosis observed through late-gadolinium enhancement images and, for the first time, a small apical aneurysm that was not clearly visualized on two-dimensional echocardiography. The time course leading to the development of an ApHCM aneurysm is not well-defined and may impact the clinical course.